DIAGNOSTIC VALUE OF SERUM BILIRUBIN IN PREDICTING COMPLICATION IN ACUTE APPENDICITIS; A PROSPECTIVE STUDY AT ABUBAKAR TAFAWA BALEWA UNIVERSITY TEACHING HOSPITAL BAUCHI, NIGERIA. - Muktar , Umar; Bello , MB (Global Journal of Medical and Health Science, 2024)
Background: Appendicitis is a common surgical emergency. Despite the increasing use of advanced imaging techniques, the rates of misdiagnosis of appendicitis (15%) and appendiceal rupture remain unchanged. The significance of hyperbilirubinemia as a predictive factor of acute appendicitis has continued to gain attention in recent studies; however, its value in the diagnosis of perforated/gangrenous appendicitis has not been studied in our practice. We studied the diagnostic value of serum bilirubin in predicting complications of acute appendicitis. Methods: This prospective study was conducted at the Surgery Department of Abubakar Tafawa Balewa University Teaching Hospital (ATBUTH) Bauchi, Nigeria over a duration of three calendar years from January 2020 to December 2022. Results: A total of 396 patients who met the predefined inclusion criteria were included in the analysis. The mean age of 24 ± 10 years, and the male-to-female ratio was 1.4:1. The majority of patients (63.7%) had non-perforated appendicitis. Notably, among the patients with a normal appendix, the percentage of female patients (69.44%) was significantly higher. 107 (29.72%) exhibited hyperbilirubinemia, and among the patients diagnosed with perforated appendicitis, 62 (86.11%) had hyperbilirubinemia. Significantly more patients with appendiceal perforation had hyperbilirubinemia than those with acute perforated appendicitis (86.11% vs. 17.36%, p < 0.001). Bilirubin demonstrated a higher specificity (97.29%) in detecting acute appendicitis, but it has a low sensitivity. A comparative analysis of serum bilirubin levels to discriminate between acute appendicitis and perforated/gangrenous appendicitis demonstrated sensitivity and specificity of 86.11% and 82.63%. A statistical analysis indicated that patients with perforated/gangrenous appendicitis were 4.96 times more likely to have hyperbilirubinemia than those with acute appendicitis. Conclusions- There is a significant difference in bilirubin levels between the patients diagnosed with acute appendicitis and those diagnosed with perforated appendicitis. Bilirubin is a valuable armamentarium for the diagnosis of perforation or gangrene